تقدير القيمة المعرضة للخطر المعدلة بالسيولة (l-var): دراسة حالة البنك الخارجي الجزائري - باهي, نوال; أيمن, فريد (جامعة الوادي - University of Eloued, 2022)
This study aims to shed light on estimating the market liquidity risk of the External Bank of Algeria BEA using the liquidity-Adjusted Value at Risk metric )L-VaR(, by taking a comprehensive view of liquidity risk and studying L-VaR estimation methods and comparing them to extract the best one, and then trying to apply The latter is at the level of the External Bank of Algeria, starting from estimating the value at risk of the bank’s portfolio using the historical simulation method, and then determining transaction costs to later study the impact of the retention period on L-VaR, based on the case study approach and the use of Excel to analyze data. It has been found through this study that the best approaches are the transaction costs approach and the liquidity discount methods, followed by the external diffusion. However, it is better to use a group of approaches instead of a single approach to highlight the various liquidity concerns.
Liquidity-adjusted Value-at-Risk (L-VAR) estimation: a case study of the External Bank of Algeria (BEA)
مقال
Keywords: مخاطر السيولة ; تقدير المخاطر ; تكاليف المعاملات ; القيمة المعرضة للخطر المعدلة بالسيولة; liquidity risk ؛risk assessment؛ transaction costs؛ liquidity-adjusted Value at Risk.